Combining mechanical interlocking, force fit and direct adhesion in polymer–metal-hybrid structures – Evaluation of the deformation and damage behavior. (May 2015) - Paul, Hanna; Luke, Michael; Henning, Frank
Abstract: The joint of long fiber reinforced thermoplastic polymer–metal-hybrid structures is evaluated. For this the deformation and damage behavior of joints combining mechanical interlocking, force fit and direct adhesion is determined experimentally. Results show that each joining mechanism results in a specific deformation and damage behavior. Experimental results also show that the behavior of the combination is dependent on the interaction of the single joining mechanisms. With finite element simulations the deformation and damage behavior of joints with combined mechanism has been evaluated beyond the tested configurations. It is demonstrated how the developed simulation tool can be used to support the selection of the best joint configurations.